2021
DOI: 10.3389/fgene.2021.639905
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Environmental Factors and Asthma Using Mendelian Randomization: Increased Effect of Body Mass Index on Adult-Onset Moderate-to-Severe Asthma Subtypes

Abstract: Although asthma is one of the most common chronic diseases throughout all age groups, its etiology remains unknown, primarily due to its heterogeneous characteristics. We examined the causal effects of various environmental factors on asthma using Mendelian randomization and determined whether the susceptibility to asthma due to the causal effect of a risk factor differs between asthma subtypes, based on age of onset, severity of asthma, and sex. We performed Mendelian randomization analyses (inverse variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The effectiveness of the IVW method in finding causal effects is higher than that of weighted median method and MR-Egger analysis [ 28 ]. However, due to the strong assumptions that the IVW method relies on, the type I error rate of causal effect estimation and the bias of the estimated value of causal effect are caused by the IVW method [ 29 ]. The MR-Egger method is greatly affected by the inside hypothesis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the IVW method in finding causal effects is higher than that of weighted median method and MR-Egger analysis [ 28 ]. However, due to the strong assumptions that the IVW method relies on, the type I error rate of causal effect estimation and the bias of the estimated value of causal effect are caused by the IVW method [ 29 ]. The MR-Egger method is greatly affected by the inside hypothesis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, UPF consumption may increase exposure to chemicals used in packaging and production and many non-natural ingredients and additives such as flavours, colours, emulsifiers, and other cosmetic additives, which could lead to adverse health outcomes [ 39 , 40 ]. Fourth, a higher proportion of UPF consumption denoted a lower proportion of fresh vegetables, fruits, and essential micronutrients, which plays key roles in supporting the human immune system and reducing the risk of infections [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies were conducted in adults and three in children. Ten out of the 12 studies showed a causal association between genetically higher BMI and increased risk of asthma 15–18,20–25 . The pooled risk ratio (RR) for asthma for 1 kg/m 2 increment in BMI was 1.05 (95% CI: 1.03–1.07) (Figure 2, Supplementary Figure 2), with overall evidence graded of high certainty (Supplementary Table 3).…”
Section: Causal Risk Factors For Asthma and Respiratory Allergymentioning
confidence: 99%
“…As a case in Granell et al, 13 the sample size was small with only 5364 participants and there were no information on MR method or sensitivity analyses. The highest scores were awarded to wellpowered and -designed studies such as the studies from Ha et al, Shen et al, and Au Yeung et al [14][15][16]…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%